Media Papan Labirin: Solusi Kreatif Meningkatkan Pemahaman Penjumlahan dan Pengurangan pada Siswa Kelas III SD - Patri Janson Silaban; Israil Sitepu; Sumber Napitupulu; Kristina Simanullang; Perinandita Banjarnahor; Yovita Nada Sipayung; Riana Saputri Saragih (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to improve the mathematics learning outcomes of third-grade elementary school students on addition and subtraction through the implementation of a maze board media. The activity used a participatory and collaborative approach, actively involving teachers and students in the learning process. The subjects were 20 third-grade students, and the object was the enhancement of understanding and mathematics learning outcomes. Data collection methods included pretest and posttest assessments and observation of student and teacher activities. The analysis results showed an increase in the average score from 61.5 in the pretest to 89.5 in the posttest, with an improvement percentage of approximately 45%. Most students showed a 30-point increase, and all students demonstrated positive progress. Furthermore, observations revealed improvements in student motivation, focus, and collaboration, as well as teachers’ ease in guiding the learning process. In conclusion, the maze board media is effective as an innovative learning strategy that enhances conceptual understanding in mathematics and creates interactive, enjoyable, and meaningful learning.